Spectrum of childhood ocular trauma in eastern region of Nepal - Gurung, Govind; Tulsyan, Nitin; Gupta, Krishna Kant (Journal of Chitwan Medical College, 2021)
Background: Pediatric ocular trauma is a significant cause of morbidity. It is estimated that there are up to 280,000 hospital admissions worldwide due to ocular trauma in children <16 years of age each year. This study was aimed to describe the spectrum of ocular trauma in children who previously visited the Pediatric Department of the Ram Kumar Mahabir prasad Kedia Eye Hospital. Methods: A retrospective study was conducted on cases coming to Pediatric Department of the Ram Kumar Mahabir prasad Kedia Eye Hospital from five years. All cases of children <15years who previously underwent evaluation and/or treatment because of ocular trauma were analyzed. Demographic and descriptive ophthalmologic data were taken out of patient records of Ram Kumar Mahabir Prasad Kedia Eye Hospital. All data were tabulated using Microsoft Excel version 7 sheets and analyzed. Results: In this study, among 55,159 children who attended Pediatric Outpatient department of Ram Kumar Mahabir Prasad Kedia Eye Hospital 3,048 had ocular injury. There were 64.7% boys and 35.2% girls. Close globe injury was seen in 84.35% and open globe injury in 15.64 %. Children aged 7-15 years were involved in 60.8% while 39.2% children were of age 6 years or less. Conclusions: Ocular injuries seems to be serious in Terai region. Children of all age group are prone to ocular injuries. Though open globe injury is less than close globe injury in this study, open globe injury is more sight threatening.